Identifying and realising the benefits of smart infrastructure and construction. Issue 4 (14th April 2021) - Pocock, David
Abstract : The Centre for Smart Infrastructure and Construction at Cambridge University in the UK is developing and demonstrating an exciting range of applications of 'smart' technology applications in infrastructure and construction. Infrastructure developers, operators and users face a wide range of risks, to which the centre's achievements can be applied, yielding valuable benefits throughout the continuous asset lifecycle. Benefits are derived in the design phase by avoiding over-design; in the construction phase by validating as-built quality and performance; and in the operational phase by better use of existing assets, diagnosis of cracking, and intelligent assets that sense and respond to their own condition. This paper identifies how are derived through direct cost savings and a wide range of potential indirect routes, both to developers and managers of existing assets, and ultimately to the end users. Most of the indirect benefits can also be monetised to some extent, to compare with the cost of the intervention as benefit:cost ratios. Further possibilities exist for avoiding costs in service through combining smart technology with engineering knowledge of the expected behaviour, deterioration and failure patterns of assets in service.